Socio-cultural perception of robot backchannels - Engwall, Olov; Cumbal, Ronald; Majlesi, Ali Reza (Frontiers in Robotics and AI, 2023)
Backchannels, i.e., short interjections by an interlocutor to indicate attention, understanding or agreement regarding utterances by another conversation participant, are fundamental in human-human interaction. Lack of backchannels or if they have unexpected timing or formulation may influence the conversation negatively, as the speaker may conclude that the interlocutor is not listening, understanding or agreeing. However, several studies over the years have shown that there may be cultural differences in how backchannels are provided and perceived and that these differences may affect intercultural conversations. Culturally aware robots must hence be endowed with the capability to detect and adapt to the way these conversational markers are used across different cultures. Traditionally, culture has been defined in terms of nationality, but this is more and more considered to be a stereotypic simplification. We therefore investigate several socio-cultural factors, such as the participants' gender, age, first language, extroversion and familiarity with robots, that may be relevant for the perception of backchannels. We first cover existing research on cultural influence on backchannel formulation and perception in human-human interaction and on backchannel implementation in Human-Robot Interaction. We then present an experiment on second language spoken practice, in which we investigate how backchannels from the social robot Furhat influence interaction and impression of the robot. The experiment, made in a triad game setting where two human players describe the meaning of a word until the robot finds the correct term, is focused on if activity-adaptive robot backchannels change the speakers’ activity compared to when backchannels are administered proportionally to speaking time according to fixed rules, and/or if the participants' assessment of the robot is influenced. We find that a strategy that displays more backchannels towards a less active speaker may substantially decrease the difference in speaking time between the two speakers, that different socio-cultural groups respond differently to the robot's backchannel strategy and that they also perceive the robot differently after the session. We conclude that the robot may need different backchanneling strategies towards speakers from different socio-cultural groups in order to encourage them to speak and to have a positive perception of the robot.